On the consumption of OTT services in India: insights from technology acceptance model and the uses and gratifications theory - Kriti Priya Gupta; Deepika Joshi; Shikha Singh (Innovation & Management Review, 2025)
The study explores the factors influencing consumers' motivation to use video streaming services of over-the-top (OTT) platforms and their willingness to pay for those services.Using a sample of 256 Indian consumers of OTT services, the study empirically tests a research framework based on the technology acceptance model (TAM) and uses and gratifications theory (UGT). Partial least squares structural equation modeling (PLS-SEM) method was used to analyze the primary data and explain consumers' motivations toward the OTT services.The findings suggest that consumers' intentions to use OTT services are determined by both extrinsic as well as intrinsic factors. However, their motivations to pay for OTT services are strongly linked with intrinsic factors such as instrumental use, interactive control and flow experience.The research focuses largely upon the individual motivations and perception towards the OTT services. It omits the prevalent communal behaviors in Indian households, where use of OTT may be considered as a shared activity. This study relies upon the data collected from urban technology savvy individuals. This may not accurately reflect the opinion of rural consumers where accessing OTT is increasing rapidly.The study will guide the global OTT players to design strategies and successfully expand their operations in emerging markets.This paper contributes to the literature by explaining the attitudes of Indian consumers toward OTT services.
Keywords: 650; Over-the-top; Technology acceptance model; Uses and gratifications; Online streaming; Intention to use and pay